2016
DOI: 10.1108/jaar-09-2013-0071
|View full text |Cite
|
Sign up to set email alerts
|

The moderating effects of environmental risk of the industry on the relationship between corporate environmental and financial performance

Abstract: Purpose – Industries differ in their environmental impacts, such as emissions, water and energy use, fuel consumption and hazardous wastes, which will have implications for how environmental performance translates to operating performance and market value at company level. By incorporating industry-specific differences of environmental impacts, this paper includes industry-level environmental risk as a moderating factor on the relationship between two indicators of corporate environmental perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 54 publications
6
41
0
Order By: Relevance
“…The higher the rating, the higher the ROA of the company. This result is in line with the research conducted by Al-Tuwaijri et al, (2004); Mahoney et al, (2013); Rohmah & Wahyudin, (2015); Semenova & Hassel, (2016); Suratno et al, (2007); Tristianasari & Fachrurrozie, (2014) stating that there is a significant relationship between the environmental performance and economic performance. Unlike Esita (2016), however, there is no influence between environmental performance and the corporate value.…”
Section: Influence Of Environmental Performance Toward Economic Perfosupporting
confidence: 88%
“…The higher the rating, the higher the ROA of the company. This result is in line with the research conducted by Al-Tuwaijri et al, (2004); Mahoney et al, (2013); Rohmah & Wahyudin, (2015); Semenova & Hassel, (2016); Suratno et al, (2007); Tristianasari & Fachrurrozie, (2014) stating that there is a significant relationship between the environmental performance and economic performance. Unlike Esita (2016), however, there is no influence between environmental performance and the corporate value.…”
Section: Influence Of Environmental Performance Toward Economic Perfosupporting
confidence: 88%
“…Prior studies found that companies from high-risk industries tend to disclose more environmental information than companies from lowrisk industries (Djajadikerta & Trireksani, 2012;Semenova & Hassel, 2016). The underlying assumption is that companies that have higher pollution propensity are required to comply with more rigorous legal requirements.…”
Section: B/e Disclosure and Industry Sectormentioning
confidence: 99%
“…Prior empirical studies suggest that large firms tend to exhibit diseconomies of scale, because of complex processes of decision-making, coordination and resource allocation and costly structural changes, and find a negative association between firm size and corporate financial performance [101,109]. Therefore, we control for firm size (Lsize), calculated as the natural logarithm of firm's total assets [109].…”
Section: Control Variablesmentioning
confidence: 99%
“…This database, founded in 2003, collects and compiles publicly available information on firms' CSR strategies using 750 individual data points, combined into over 280 key performance indicators from over 4612 large firms distributed around the world and belonging to several industries. The ASSET4 database has been used in [15,18,101,102], among others. On the other hand, Worldscope database provides information on over 58,000 firms, with more than 37,000 of them active, which are included in this database on meeting at least one of these criteria: (1) their market capitalization must be greater than US$100 million; (2) they must be a member of one or more global or local indexes; (3) they must be quoted on many stock markets; and (4) they must have high visibility.…”
Section: Samplementioning
confidence: 99%